Fiber sizing agent, fiber bundle, fiber product, resin composition and molded body
The modified resin sizing agent for fibers addresses the strength issue in fiber-reinforced composite materials by enhancing cohesiveness and strength, ensuring superior performance in molded objects with improved moldability and heat resistance.
Patent Information
- Application Number
- JP2024189660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-01-29
AI Technical Summary
Existing sizing agents for fibers do not adequately enhance the strength of fiber-reinforced composite materials, particularly when used with thermoplastic resins that require high heat resistance.
A sizing agent for fibers containing modified polyarylate, polysulfone, polyethersulfone, aromatic polyimide, and aromatic polyetherimide resins, with functional groups such as (poly)oxyalkylene, sulfo, carboxyl, and 1,3-dioxo-2-oxapropylene groups, applied to carbon, glass, aramid, or ceramic fibers, forming fiber bundles with improved cohesiveness and strength.
The modified resin sizing agent enhances the strength and cohesiveness of fiber bundles, resulting in superior strength and appearance of molded objects, while maintaining excellent moldability and heat resistance.
Smart Images

Figure 2025010274000001 
Figure 2025010274000002 
Figure 2025010274000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber sizing agent, a fiber bundle, a fiber product, a resin composition, and a molded article. [Background technology]
[0002] Because carbon fibers and glass fibers are lightweight and have excellent strength and elastic modulus, fiber-reinforced composite materials made by combining these with various matrix resins are widely used in the fields of sports equipment, leisure goods, aircraft, etc. In recent years, they have also begun to be used in engines, automobile parts, electronics, and the machinery industry, etc., where higher heat resistance is required, and it is important that fiber-reinforced composite materials have excellent moldability in addition to heat resistance and physical properties. Meanwhile, thermosetting resins such as epoxy resins, vinyl ester resins, unsaturated polyester resins and phenol resins have traditionally been the mainstream of matrix resins used in fiber-reinforced composite materials. However, from the viewpoint of moldability, polypropylene resins, polyamide resins, polycarbonate resins and polyphenylene sulfide resins have recently been used, and in particular, for carbon fiber-reinforced composite materials, polyetherimide resins and polyether ether ketone resins, which have high heat resistance with molding temperatures exceeding 350°C, are beginning to be used.
[0003] As sizing agents used to reinforce these thermoplastic resins with carbon fibers, those containing polycarbonate resins or imide resins having a siloxane structure (e.g., Patent Documents 1 and 2) and those containing aromatic polyester-based urethane resins (e.g., Patent Document 3) have been proposed. However, even with the techniques described in the patent documents, there was a problem in that the strength of the composite material was not fully developed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-57640 [Patent Document 2] Japanese Patent Application Publication No. 6-2279 [Patent Document 3] Patent No. 5802834 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a fiber sizing agent which imparts excellent strength to a molded article. [Means for solving the problem]
[0006] The present inventors conducted research aimed at achieving the above object and arrived at the present invention. That is, the present invention relates to a fiber sizing agent containing at least one modified resin (B) of resin (A) selected from the group consisting of polyarylate resin (A2), polysulfone resin (A3), polyethersulfone resin (A4), aromatic polyimide resin (A5), aromatic polyetherimide resin (A6), aromatic polyetherketone resin (A7), aromatic polyetheretherketone resin (A8) and aromatic polyetherketoneketone resin (A9), wherein the modified resin (B) is a modified resin (B) selected from the group consisting of a (poly)oxyalkylene group, a sulfo group, a carboxyl group and a 1,3-dioxo-2-oxapropylene group in the resin (A). a fiber sizing agent in which the modified resin (B) has been introduced with at least one functional group selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, rock fibers, and slag fibers, and which exhibits a heat loss ratio of 20% by weight or less at 400°C when heated in nitrogen up to 500°C under conditions of a heating start temperature of 30°C and a heating rate of 5°C / min; a fiber bundle in which at least one fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, rock fibers, and slag fibers has been treated with the fiber sizing agent; a fiber product containing the fiber bundle; a resin composition containing the fiber bundle and / or the fiber product and a thermoplastic resin (E); and a molded product obtained by molding the resin composition. Effect of the Invention
[0007] The fiber sizing agent of the present invention has the following effects. - Gives excellent strength to the molded body. Gives excellent appearance to molded products. - Gives excellent bundling properties to fiber bundles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] <Textile sizing agent> The fiber sizing agent of the present invention is a fiber sizing agent containing a modified product (B) of at least one resin (A) selected from the group consisting of polyphenylene ether resin (A1), polyarylate resin (A2), polysulfone resin (A3), polyethersulfone resin (A4), aromatic polyimide resin (A5), aromatic polyetherimide resin (A6), aromatic polyetherketone resin (A7), aromatic polyetheretherketone resin (A8) and aromatic polyetherketoneketone resin (A9), wherein the modified product (B) is a modified resin obtained by introducing at least one functional group selected from the group consisting of a (poly)oxyalkylene group, a sulfo group, a carboxyl group and a 1,3-dioxo-2-oxapropylene group into the resin (A), and wherein the modified product (B) has a heat loss ratio of 20% by weight or less at 400°C when heated in nitrogen under conditions of a heating start temperature of 30°C and a heating rate of 5°C / min up to 500°C.
[0009] The polyphenylene ether resin (A1) is a resin having a structure obtained by polycondensation of an aromatic compound (a12) having two hydroxyl groups, and includes a resin obtained by oxidative coupling polymerization of an aromatic compound (a11) having one hydroxyl group and / or an aromatic compound (a12) having two hydroxyl groups.
[0010] The aromatic compound (a11) having one hydroxyl group includes a compound in which one hydroxyl group is directly bonded to an aromatic ring, and specifically includes a compound in which at least two hydrogen atoms (preferably at the 2- and 6-positions) of a phenol are substituted with at least one group selected from the group consisting of an alkyl group having 1 to 30 carbon atoms, an aryl group having 6 to 30 carbon atoms, and an aralkyl group having 7 to 30 carbon atoms. Examples of the alkyl group having 1 to 30 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, a sec-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, an n-decyl group, an n-undecyl group, an n-dodecyl group, an n-tridecyl group, an n-tetradecyl group, an n-pentadecyl group, an n-hexadecyl group, an n-heptadecyl group, an n-octadecyl group, an n-nonadecyl group, an n-icosyl group, and an n-triacontyl group. Examples of the aryl group having 6 to 30 carbon atoms include a phenyl group, a 1-naphthyl group, and a 2-naphthyl group. Examples of the aralkyl group having 7 to 30 carbon atoms include a benzyl group, a phenylmethyl group, and a phenylethyl group.
[0011] Specific examples of the aromatic compound (a11) include 2,6-dimethylphenol (sometimes referred to as 2,6-xylenol), 2,6-diethylphenol, 2,6-dipropylphenol, 2,6-dibutylphenol, 2,6-dipentylphenol, 2,6-dihexylphenol, 2,6-diheptylphenol, 2,6-dioctylphenol, 2,6-dinonylphenol, 2,6-didecylphenol, 2,6-didodecylphenol, 2,6-ditetradecylphenol, 2, Examples of the dialkylphenols include 6-dihexadecylphenol, 2,6-dioctadecylphenol, 2,6-diicosylphenol, 2,6-ditriacontylphenol, 2-methyl-6-ethylphenol, and 2,5-dimethylphenol; diarylphenols such as 2,6-diphenylphenol, 2,6-dinaphthylphenol, and 2,5-diphenylphenol; and diaralkylphenols such as 2,6-dibenzylphenol and 2,6-diphenylethylphenol.
[0012] The aromatic compound (a12) having two hydroxyl groups includes a compound in which two hydroxyl groups are directly bonded to one aromatic ring and a compound in which two aromatic rings each having a hydroxyl group directly bonded to an aromatic ring are bonded. Specific examples thereof include hydroquinone, naphthalenediol (e.g., 2,7-naphthalenediol, etc.), 4,4'-biphenol, bisphenol S [bis(4-hydroxyphenyl)sulfone], compounds in which a hydroxyaryl group is bonded via a divalent hydrocarbon group having 1 to 20 carbon atoms (including those in which a portion of the hydrogen atoms of the hydrocarbon group is substituted with a halogen group) and derivatives thereof (e.g., those in which a hydrogen atom bonded to an aromatic ring is substituted with a hydrocarbon group having 1 to 20 carbon atoms) (a121), an aromatic compound (a122) in which two aromatic rings each having a hydroxyl group directly bonded to an aromatic ring are bonded via a carbonyl group, and an aromatic compound (a123) in which two aromatic rings each having a hydroxyl group directly bonded to an aromatic ring are bonded via an ether bond. In (a121), examples of the divalent hydrocarbon group having 1 to 20 carbon atoms include alkylene groups having 1 to 20 carbon atoms (e.g., methylene group, ethylene group, 1,2- or 1,3-propylene group, and 1,2-, 1,3-, 1,4- or 2,3-butylene group), cycloalkylene groups having 3 to 20 carbon atoms (e.g., 1,2-, 1,3- or 1,4-cyclohexylene group), divalent aromatic hydrocarbon groups having 6 to 20 carbon atoms (e.g., 1,2-, 1,3- or 1,4-phenylene group), and divalent aromatic-aliphatic hydrocarbon groups having 7 to 20 carbon atoms (e.g., 1-methyl-2,3-phenylene group). Specific examples of (a121) include those bonded via an alkylene group {for example, bisphenol F (1,1-bis(4-hydroxyphenyl)methane), tetramethylbisphenol F (1,1-bis(4-hydroxy-3,5-dimethylphenyl)methane), bisphenol E (1,1-bis(4-hydroxyphenyl)ethane), tetramethylbisphenol E (1,1-bis(4-hydroxy-3,5-dimethylphenyl)ethane), bisphenol A (2,2-bis(4-hydroxyphenyl)propane), tetramethylbisphenol A (2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane), bisphenol B (2,2-bis(4-hydroxyphenyl)butane), tetramethylbisphenol B (2,2-bis(4-hydroxy-3,5-dimethylphenyl)butane), bisphenol C (2,2-bis(3-methyl-4-hydroxyphenyl)propane), bisphenol G (2,2 -bis(4-hydroxy-3-isopropylphenyl)propane), bisphenol PH (5,5'-(1-methylethylidene)-bis[1,1'-(bisphenyl)-2-ol]propane), etc.}, those bonded via a cycloalkylene group {bisphenol Z (1,1-bis(4-hydroxyphenyl)cyclohexane), bisphenol TMC (1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane), etc.}, bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane), bisphenol BP (bis(4-hydroxyphenyl)diphenylmethane), bisphenol M (1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene), bisphenol P (1,4-bis(2-(4-hydroxyphenyl)-2-propyl)benzene), bisphenol AF (2,2-bis(4-hydroxyphenyl)hexafluoropropane), etc. Specific examples of (a122) include 4,4'-dihydroxybenzophenone and 2,4'-dihydroxybenzophenone. Specific examples of (a123) include 4,4'-dihydroxyphenyl ether.
[0013] In the polyphenylene ether resin (A1), among the aromatic compounds (a11), dialkylphenols are preferred from the viewpoint of emulsion stability of the modified product (B), and 2,6-dimethylphenol and 2,6-diethylphenol are more preferred. The polyphenylene ether resin (A1) can be obtained by a known method (for example, JP 2019-189686 A, etc.). As the polyphenylene ether resin (A1), Noryl (manufactured by SABIC) and Zylon (manufactured by Asahi Kasei Corporation) are commercially available and are available.
[0014] The polyarylate resin (A2) is a resin having a structure obtained by polycondensation of an aromatic compound (a12) having two hydroxyl groups and an aromatic compound (a22) having two carboxyl groups, and includes resins obtained by an esterification reaction between (a12) and (a22) and an esterification reaction between (a12) and an aromatic compound (a72) having two halogenated acyl groups obtained by converting the carboxyl groups of (a22) to acid chlorides (halogenated acyl groups).
[0015] Examples of the aromatic compound (a12) having two hydroxyl groups include the compounds exemplified above in the description of the polyphenylene ether resin (A1). In the polyarylate resin (A2), from the viewpoint of the appearance of the molded product, the aromatic compound (a12) having two hydroxyl groups is preferably naphthalenediol, bisphenol S, a compound in which a hydroxyaryl group is bonded via a divalent hydrocarbon group having 1 to 20 carbon atoms, or a derivative (a121) thereof, and more preferably a compound in which a hydroxyaryl group is bonded via a divalent hydrocarbon group having 1 to 20 carbon atoms, or a derivative (a121) thereof.
[0016] The aromatic compound (a22) having two carboxyl groups is a compound having two carboxyl groups directly bonded to an aromatic ring, and an aromatic compound having two aromatic rings each having a carboxyl group directly bonded to the aromatic ring, and includes aromatic dicarboxylic acids having 8 to 40 carbon atoms. Specific examples thereof include phthalic acid, isophthalic acid, terephthalic acid, diphenyl ether dicarboxylic acid (e.g., diphenyl ether-2,2'-dicarboxylic acid, diphenyl ether-2,3'-dicarboxylic acid, diphenyl ether-2,4'-dicarboxylic acid, diphenyl ether-3,3'-dicarboxylic acid, diphenyl ether-3,4'-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, etc.), naphthalenedicarboxylic acid (e.g., 1,5-naphthalenedicarboxylic acid and 2,6-naphthalenedicarboxylic acid, etc.), and derivatives, acid anhydrides, and lower alkyl (having 1 to 4 carbon atoms) esters of these dicarboxylic acids. In the present invention, examples of the derivative include those in which a hydrogen atom bonded to an aromatic ring is substituted with a hydrocarbon group having 1 to 20 carbon atoms. Examples of the hydrocarbon group having 1 to 20 carbon atoms include an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms.
[0017] In the polyarylate resin (A2), from the viewpoint of the emulsion stability of the modified product (B), among the aromatic compounds (a22), phthalic acid, isophthalic acid, terephthalic acid and diphenyl ether dicarboxylic acid are preferred, and phthalic acid, isophthalic acid and terephthalic acid are more preferred.
[0018] The aromatic compound (a72) having two halogenated acyl groups includes the aromatic compound (a22) having a carboxyl group converted into an acid chloride (halogenated acyl group), and specifically includes phthalic acid dichloride, isophthalic acid dichloride, terephthalic acid dichloride, an aromatic compound (a721) having two aromatic rings bonded together and one halogenated acyl group bonded directly to the aromatic ring {e.g., diphenyl ether dicarboxylic acid dichloride (e.g., diphenyl ether-2,2'-dicarboxylic acid dichloride, diphenyl ether-2,3'-dicarboxylic acid dichloride, diphenyl ether-2,4'-dicarboxylic acid dichloride, diphenyl ether-3,3'-dicarboxylic acid dichloride, diphenyl ether-3,4'-dicarboxylic acid dichloride, diphenyl ether-4,4'-dicarboxylic acid dichloride, etc.}, naphthalene dicarboxylic acid dichloride (for example, 1,5-naphthalene dicarboxylic acid dichloride and 2,6-naphthalene dicarboxylic acid dichloride, etc.), 4,4'-(1,4-phenylenebisoxy)bis(benzoic acid chloride), 4,4'-(1,2-phenylenebisoxy)bis(benzoic acid chloride), 4,4'-(1,3-phenylenebisoxy)bis(benzoic acid chloride), 4,4'-[(2,6-naphthalene diyl)bisoxy]bis(benzoic acid chloride), 4,4'-[(1,5-naphthalene diyl)bisoxy]bis(benzoic acid chloride), and 4,4'-[(1,4-naphthalene diyl)bisoxy]bis(benzoic acid chloride), as well as derivatives of these dicarboxylic acid dichlorides.
[0019] In the polyarylate resin (A2), from the viewpoint of the emulsion stability of the modified product (B), among the aromatic compounds (a72), phthalic acid dichloride, isophthalic acid dichloride, terephthalic acid dichloride and diphenyl ether dicarboxylic acid dichloride are preferred, and phthalic acid dichloride, isophthalic acid dichloride and terephthalic acid dichloride are more preferred.
[0020] The polyarylate resin (A2) may contain residues of other components such as aliphatic diols, alicyclic diols, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids. Examples of aliphatic diols include ethylene glycol and propylene glycol. Examples of alicyclic diols include 1,4-cyclohexanediol, 1,3-cyclohexanediol, and 1,2-cyclohexanediol. Examples of aliphatic dicarboxylic acids include adipic acid and sebacic acid. Examples of alicyclic dicarboxylic acids include 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,2-cyclohexanedicarboxylic acid. The content of residues of other components is preferably less than 10 mol% relative to the total mole number of raw material monomers, and more preferably is substantially free of residues.
[0021] The polyarylate resin (A2) can be obtained by a known method (for example, JP-A No. 2010-65155). As the polyarylate resin (A2), Unifiner (manufactured by Unitika Ltd.) is commercially available.
[0022] The polysulfone resin (A3) is a resin having a structure obtained by polycondensation of an aromatic compound (a12) having two hydroxyl groups and an aromatic compound in which two aromatic rings are bonded via a sulfonyl group, and includes a resin obtained by desalting polycondensation of (a12) and an aromatic compound (a52) in which two aromatic rings, each having a halogen group bonded directly to the aromatic ring, are bonded via a sulfonyl group.
[0023] Examples of the aromatic compound (a12) having two hydroxyl groups include the compounds exemplified in the description of the polyphenylene ether resin (A1). In the polysulfone resin (A3), the aromatic compound (a12) having two hydroxyl groups is preferably naphthalenediol, bisphenol S, a compound in which a hydroxyaryl group is bonded via a divalent hydrocarbon group having 1 to 20 carbon atoms, or a derivative (a121) thereof, or an aromatic compound (a122) in which two aromatic rings each having a hydroxyl group bonded directly to the aromatic ring are bonded via a carbonyl group, from the viewpoint of the appearance of the molded product, and more preferably a compound in which a hydroxyaryl group is bonded via a divalent hydrocarbon group having 1 to 20 carbon atoms, or a derivative (a121) thereof, or an aromatic compound (a122) in which two aromatic rings each having a hydroxyl group bonded directly to the aromatic ring are bonded via a carbonyl group.
[0024] The aromatic compound (a52) in which two aromatic rings each having a halogen group bonded directly to the aromatic ring are bonded via a sulfonyl group includes those having 12 to 40 carbon atoms, and specific examples thereof include 4,4'-dichlorodiphenyl sulfone, 3,4'-dichlorodiphenyl sulfone, and 4,4'-bis(4-chlorophenylsulfonyl)biphenyl, as well as derivatives thereof (in which a hydrogen atom bonded to the aromatic ring is substituted with a hydrocarbon group having 1 to 20 carbon atoms). In the polysulfone resin (A3), from the viewpoint of emulsion stability of the modified product (B), the aromatic compound (a52) is preferably 4,4'-dichlorodiphenyl sulfone or 3,4'-dichlorodiphenyl sulfone, and more preferably 4,4'-dichlorodiphenyl sulfone.
[0025] The polysulfone resin (A3) can be obtained by a known method (for example, JP 2017-226804 A, etc.). As the polysulfone resin (A3), Udel (manufactured by Solvay) is commercially available.
[0026] The polyethersulfone resin (A4) is a resin having a structure obtained by polycondensation of bisphenol S and its derivatives (in which the hydrogen atoms bonded to the aromatic rings are substituted with hydrocarbon groups having 1 to 20 carbon atoms) among aromatic compounds (a12) having two hydroxyl groups, and an aromatic compound (a5) in which two aromatic rings are bonded via a sulfonyl group, and includes resins obtained by desalting polycondensation of bisphenol S and its derivatives with an aromatic compound (a52) in which two aromatic rings having halogen groups bonded directly to the aromatic rings are bonded via a sulfonyl group. Examples of the aromatic compound (a52) include the same as those mentioned above. In (A4), the aromatic compound (a52) is preferably 4,4'-dichlorodiphenyl sulfone or 3,4'-dichlorodiphenyl sulfone from the viewpoint of the emulsion stability of the modified product (B). The polyethersulfone resin (A4) can be obtained by a known method (for example, JP-A-3-95220, etc.). As the polyethersulfone resin (A4), Sumikaexcel (manufactured by Sumitomo Chemical Co., Ltd.) is commercially available and is available.
[0027] The aromatic polyimide resin (A5) is a resin having a structure obtained by polycondensation of an aromatic compound (a32) having two amino groups and an aromatic compound (a42) having two 1,3-dioxo-2-oxapropylene groups, and is a resin obtained by a ring-opening polyaddition and dehydration cyclization reaction between (a32) and (a42), and includes those other than the aromatic polyetherimide resin (A6) described later.
[0028] The aromatic compound (a32) having two amino groups has a carbon number of 6 to 40 and includes an aromatic compound having two amino groups directly bonded to one aromatic ring and an aromatic compound having two aromatic rings each having an amino group directly bonded to an aromatic ring. Specific examples of the aromatic compound (a32) include phenylenediamine (e.g., o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, etc.), 2,4-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylether, 3,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-diaminobenzophenone, 3,3'-diaminobenzofuran, phenylene, 4,4'-bis(4-aminophenyl)sulfide, 4,4'-diaminodiphenylsulfone, 4,4'-diaminobenzanilide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 2,2'-bis(4-(4-aminophenoxy)phenyl)propane, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, and derivatives thereof (wherein the hydrogen atoms bonded to the aromatic ring are substituted with a hydrocarbon group having 1 to 20 carbon atoms).
[0029] In the aromatic polyimide resin (A5), from the viewpoint of emulsion stability of the modified product (B), among the aromatic compounds (a32) having two amino groups, phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-bis(3-aminophenoxy)biphenyl and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl are preferred, and phenylenediamine and 4,4'-bis(3-aminophenoxy)biphenyl are more preferred.
[0030] Examples of the aromatic monomer (a42) having two 1,3-dioxo-2-oxapropylene groups include a compound having 8 to 40 carbon atoms and having two 1,3-dioxo-2-oxapropylene groups directly bonded to one aromatic ring, and an aromatic compound having two aromatic rings bonded to each other and each having a 1,3-dioxo-2-oxapropylene group directly bonded to the aromatic ring. Specific examples of the aromatic monomer (a42) include pyromellitic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2 -bis(2,3-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, and derivatives thereof (wherein the hydrogen atoms bonded to the aromatic rings are substituted with hydrocarbon groups having 1 to 20 carbon atoms).
[0031] In the aromatic polyimide resin (A5), from the viewpoint of emulsion stability of the modified product (B), the aromatic compound (a42) having two 1,3-dioxo-2-oxapropylene groups is preferably pyromellitic dianhydride, 2,3',3,4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride and 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, more preferably pyromellitic dianhydride, 2,3',3,4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride and 3,3',4,4'-benzophenone tetracarboxylic dianhydride.
[0032] The aromatic polyimide resin (A5) can be obtained by a known method (for example, JP-A No. 2007-16182). As the aromatic polyimide resin (A5), UIP (manufactured by Ube Industries, Ltd.) is commercially available and is available.
[0033] The aromatic polyetherimide resin (A6) is a resin having a structure obtained by polycondensation of an aromatic compound (a32) having two amino groups and an aromatic compound (a421) in which two aromatic rings having a 1,3-dioxo-2-oxapropylene group directly bonded to the aromatic ring are bonded via an ether bond, and includes a resin obtained by ring-opening polyaddition and dehydration cyclization reaction of (a32) and (a421).
[0034] Examples of the aromatic compound (a32) having two amino groups include the same compounds as those exemplified in the description of the aromatic polyimide resin (A5). In the aromatic polyetherimide resin (A6), from the viewpoint of emulsion stability of the modified product (B), the aromatic compound (a32) having two amino groups is preferably phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 2,2'-bis(4-(4-aminophenoxy)phenyl)propane, and 3,3'-dimethyl-4,4'-diaminobiphenyl, and more preferably phenylenediamine and 2,2'-bis(4-(4-aminophenoxy)phenyl)propane.
[0035] The aromatic compound (a421) in which two aromatic rings each having a 1,3-dioxo-2-oxapropylene group bonded directly to the aromatic ring are bonded via an ether bond [hereinafter also referred to as "aromatic compound (a421)"] includes those having 16 to 40 carbon atoms, and specific examples thereof include 2,2-bis[4-(2,3-dicarboxyphenoxy)phenyl]propane dianhydride and 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride. In the aromatic polyetherimide resin (A6), from the viewpoint of the emulsion stability of the modified product (B), 2,2-bis[4-(2,3-dicarboxyphenoxy)phenyl]propane dianhydride and 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride are preferred as the aromatic compound (a421).
[0036] The aromatic polyetherimide resin (A6) can be obtained by a known method (for example, Japanese Patent No. 6382988, etc.). As the aromatic polyetherimide resin (A6), ULTEM (manufactured by SABIC) is commercially available.
[0037] The aromatic polyetherketone resin (A7) is a resin having a structure obtained by polycondensation of a compound (a121) in which two aromatic rings having hydroxyl groups directly bonded to the aromatic rings are bonded together, or an aromatic compound (a122) in which two aromatic rings having hydroxyl groups directly bonded to the aromatic rings are bonded together via a carbonyl group [hereinafter also referred to as "aromatic compound (a122)], and an aromatic compound (a6) in which two aromatic rings are bonded together via a carbonyl group. Examples of the aromatic polyetherketone resin (A7) include resins obtained by polycondensation of the compound (a121) or the aromatic compound (a122) with an aromatic compound (a62) in which two aromatic rings having halogen groups directly bonded to the aromatic rings are bonded together via a carbonyl group.
[0038] An example of the compound (a121) in which two aromatic rings are bonded, each having a hydroxyl group directly bonded to the aromatic ring, is 4,4'-biphenol. An example of the aromatic compound (a122) is the same as the compounds exemplified in the description of the polyphenylene ether resin (A1). In the aromatic polyether ketone resin (A7), the aromatic compound (a122) is preferably 4,4'-dihydroxybenzophenone or 2,4'-dihydroxybenzophenone from the viewpoint of emulsion stability of the modified product (B). In the aromatic polyether ketone resin (A7), the compound (a121) in which two aromatic rings having a hydroxyl group directly bonded to the aromatic ring are bonded is preferably 4,4'-biphenol.
[0039] An example of the aromatic compound (a6) in which two aromatic rings are bonded via a carbonyl group is the aromatic compound (a62) in which two aromatic rings each having a halogen group bonded directly to the aromatic ring are bonded via a carbonyl group (hereinafter also referred to as "aromatic compound (a62)").
[0040] The aromatic compound (a62) includes those having 13 to 40 carbon atoms. Specific examples thereof include 4,4'-dichlorobenzophenone, 2,4'-dichlorobenzophenone, 1,4-bis(4-chlorobenzoyl)benzene, 1,3-bis(4-chlorobenzoyl)benzene, 4,4'-difluorobenzophenone, 2,4'-difluorobenzophenone, 1,4-bis(4-fluorobenzoyl)benzene, 1,3-bis(4-fluorobenzoyl)benzene, and derivatives thereof (wherein a hydrogen atom bonded to an aromatic ring is substituted with a hydrocarbon group having 1 to 20 carbon atoms). In the aromatic polyether ketone resin (A7), from the viewpoint of the emulsion stability of the modified product (B), 4,4'-dichlorobenzophenone, 2,4'-dichlorobenzophenone, 1,4-bis(4-chlorobenzoyl)benzene, 1,3-bis(4-chlorobenzoyl)benzene, 4,4'-difluorobenzophenone, 2,4'-difluorobenzophenone, 1,4-bis(4-fluorobenzoyl)benzene and 1,3-bis(4-fluorobenzoyl)benzene are preferred as the aromatic compound (a62).
[0041] The aromatic polyether ketone resin (A7) can be obtained by a known method (for example, JP-A No. 2002-322271). As the aromatic polyether ketone resin (A7), Victrex HT (manufactured by Victrex) is commercially available and is available.
[0042] The aromatic polyether ether ketone resin (A8) is a resin having a structure obtained by polycondensation of an aromatic compound (a12) having two hydroxyl groups and an aromatic compound (a6) in which two aromatic rings are bonded via a carbonyl group. Examples of the aromatic compound (a12) having two hydroxyl groups include the above compounds exemplified in the description of the polyphenylene ether resin (A1). Examples of the aromatic compound (a6) having two aromatic rings bonded by a carbonyl group include the above compounds exemplified in the description of the aromatic polyether ketone resin (A7). The aromatic polyether ether ketone resin (A8) includes a resin obtained by a nucleophilic substitution reaction of an aromatic compound (a81) having a structure in which an aromatic ring having one hydroxyl group and an aromatic ring having one halogen group are bonded via a carbonyl group, a resin obtained by a Friedel-Crafts reaction of an aromatic compound (a71) in which an aromatic ring having one halogenated acyl group and an aromatic ring having no functional group are bonded via an ether bond, and a resin obtained by a Friedel-Crafts reaction of an aromatic compound (a721) in which two aromatic rings, each having one halogenated acyl group bonded directly to the aromatic ring, are bonded via an ether bond with diphenyl ether and its derivatives.
[0043] The aromatic compound (a81) having a structure in which an aromatic ring having one hydroxyl group and an aromatic ring having one halogen group are bonded via a carbonyl group [hereinafter also referred to as "aromatic compound (a81)"] includes aromatic compounds having 12 to 40 carbon atoms in which an aromatic ring having one hydroxyl group directly bonded to the aromatic ring and an aromatic ring having one halogen group directly bonded to the aromatic ring are bonded via a carbonyl group, and specific examples thereof include 4-chloro-4'-hydroxybenzophenone, 4-fluoro-4'-hydroxybenzophenone, and derivatives thereof (in which a hydrogen atom bonded to the aromatic ring is substituted with a hydrocarbon group having 1 to 20 carbon atoms), and the like. In the aromatic polyether ether ketone resin (A8), the aromatic compound (a81) is preferably 4-chloro-4'-hydroxybenzophenone or 4-fluoro-4'-hydroxybenzophenone from the viewpoint of the emulsion stability of the modified product (B).
[0044] The aromatic compound (a71) in which an aromatic ring having one halogenated acyl group and an aromatic ring having no functional group are bonded via an ether bond [hereinafter also referred to as "aromatic compound (a71)"] includes aromatic compounds having 13 to 40 carbon atoms in which an aromatic ring having one halogenated acyl group directly bonded to the aromatic ring and an aromatic ring in which some of the hydrogen atoms of the aromatic ring may be substituted with a hydrocarbon group having 1 to 27 carbon atoms are bonded via an ether bond, and specific examples thereof include 4-phenoxybenzoyl chloride and derivatives thereof (in which a hydrogen atom bonded to the aromatic ring is substituted with a hydrocarbon group having 1 to 20 carbon atoms). In the aromatic polyether ether ketone resin (A8), the aromatic compound (a71) is preferably 4-phenoxybenzoyl chloride from the viewpoint of the emulsion stability of the modified product (B).
[0045] Aromatic compounds (a721) in which two aromatic rings, each having one halogenated acyl group directly bonded to the aromatic ring, are bonded via an ether bond [hereinafter also referred to as "aromatic compounds (a721)"] include those having 14 to 40 carbon atoms, such as diphenyl ether-2,2'-dicarboxylic acid dichloride, diphenyl ether-2,3'-dicarboxylic acid dichloride, diphenyl ether-2,4'-dicarboxylic acid dichloride, diphenyl ether-3,3'-dicarboxylic acid dichloride, diphenyl ether-3,4'-dicarboxylic acid dichloride, diphenyl ether-4,4'-dicarboxylic acid dichloride, and derivatives thereof (in which the hydrogen atoms bonded to the aromatic rings are substituted with hydrocarbon groups having 1 to 20 carbon atoms), etc. In the aromatic polyether ether ketone resin (A8), from the viewpoint of the emulsion stability of the modified product (B), preferred aromatic compounds (a721) are diphenyl ether-2,2'-dicarboxylic acid dichloride, diphenyl ether-2,3'-dicarboxylic acid dichloride, diphenyl ether-2,4'-dicarboxylic acid dichloride, diphenyl ether-3,3'-dicarboxylic acid dichloride, diphenyl ether-3,4'-dicarboxylic acid dichloride and diphenyl ether-4,4'-dicarboxylic acid dichloride.
[0046] The aromatic polyether ether ketone resin (A8) can be obtained by a known method (for example, JP-A-2010-95614, etc.). As the aromatic polyether ether ketone resin (A8), VESTAKEEP (manufactured by Daicel-Evonik) is commercially available and is available.
[0047] The aromatic polyether ketone ketone resin (A9) is a resin having a structure obtained by polycondensation of an aromatic compound (a22) having two carboxyl groups and an aromatic compound (a123) in which two aromatic rings having hydroxyl groups bonded directly to the aromatic ring are bonded via an ether bond, and includes resins obtained by the Friedel-Crafts reaction of an aromatic compound (a72) having two halogenated acyl groups [hereinafter also referred to as "aromatic compound (a72)] with diphenyl ether and its derivatives.
[0048] Examples of (a72) include the same as above. In the aromatic polyether ketone ketone resin (A9), from the viewpoint of the appearance of the molded product, the aromatic compound (a72) is preferably one not having an ether bond (such as phthalic acid dichloride, isophthalic acid dichloride, terephthalic acid dichloride, and naphthalenedicarboxylic acid dichloride), and more preferably phthalic acid dichloride, isophthalic acid dichloride, terephthalic acid dichloride, and naphthalenedicarboxylic acid dichloride.
[0049] The aromatic polyether ketone ketone resin (A9) can be obtained by a known method (for example, US Pat. No. 3,065,205). As the aromatic polyether ketone ketone resin (A9), Kepstan (manufactured by Arkema) is commercially available and is available.
[0050] As the resin (A), from the viewpoints of the appearance of the molded product and emulsion stability, the polyphenylene ether resin (A1) and the polyarylate resin (A2) are preferred.
[0051] The glass transition temperature of resin (A) (hereinafter sometimes abbreviated as Tg) is preferably 10 to 350°C, more preferably 100 to 300°C, from the viewpoints of moldability and the strength of the molded article. The Tg of resin (A) can be measured by using a differential scanning calorimetry (DSC) apparatus (for example, "Shimadzu DSC-60" manufactured by Shimadzu Corporation) in a nitrogen atmosphere and heating at a rate of 20°C / min from 40 to 300°C in accordance with JIS K7121 (1987). Note that the Tg of resin (A) can be increased by increasing the aromatic ring concentration (weight ratio of aromatic rings in the resin), and can be decreased by increasing the number of alkyl groups or increasing the number of carbon atoms in the alkyl groups.
[0052] In the present invention, the weight average molecular weight of resin (A) (hereinafter sometimes abbreviated as Mw) is preferably 1000 to 20000, more preferably 1200 to 15000, from the viewpoints of emulsion stability and aggregability. In the present invention, Mw and the number average molecular weight (hereinafter sometimes abbreviated as Mn) can be determined in terms of polystyrene under the following conditions by using gel permeation chromatography (GPC). <Measurement conditions of GPC> Liquid delivery device: Waters Corporation, Isocratic HPLC Pump 1515 Detector: Waters Corporation, Refractive Index Detector 2414 Column: Mixed-D (packed silica gel particle size 5 μm, tube length 300 mm, inner diameter 7.5 mm) Solvent: chloroform Flow rate: 1 mL / min Measurement temperature: 35°C
[0053] The fiber aggregating agent of the present invention contains a modified product (B) of the above resin (A). In the fiber aggregating agent of the present invention, one kind of the modified product (B) may be used, or two or more kinds may be used in combination. In the present invention, the modified product (B) is a modified resin obtained by introducing at least one group selected from the group consisting of a (poly)oxyalkylene group, a sulfo group, a carboxyl group, and a 1,3-dioxo-2-oxapropylene group into the resin (A). Examples of modified resins in which a sulfo group has been introduced into resin (A) include those in which a sulfonating agent (such as chlorosulfuric acid and fuming sulfuric acid) is reacted with resin (A) to introduce a sulfo group into an aromatic ring of resin (A). In addition, examples of modified resins in which a (poly)oxyalkylene group and / or a sulfo group has been introduced into resin (A) include the following modified products depending on the type of functional group possessed by resin (A). When the resin (A) is a resin having a hydroxyl group {including a resin obtained by a reaction using an aromatic compound having a hydroxyl group, specifically, polyphenylene ether resin (A1), polyarylate resin (A2), polysulfone resin (A3), polyethersulfone resin (A4), aromatic polyether ketone (A7), aromatic polyether ether ketone resin (A8), etc.}, examples of the resin include a reaction product of a hydroxyl group with at least one selected from the group consisting of an alkylene oxide, sulfamic acid, chlorosulfuric acid, and sultones (e.g., 1,3-propane sultone, etc.). A modified product having a (poly)oxyalkylene group can be obtained by the reaction with an alkylene oxide, and a sulfo group (-SO3H) can be added to the hydroxyl group by the reaction with at least one of sulfamic acid, chlorosulfuric acid, and sultones. In the present invention, the (poly)oxyalkylene group means an "oxyalkylene group and / or a polyoxyalkylene group". In the present invention, the alkylene oxide includes those having 2 to 4 carbon atoms, and specific examples thereof include ethylene oxide (hereinafter abbreviated as EO), 1,2- or 1,3-propylene oxide (hereinafter abbreviated as PO), 1,2-, 1,3-, 1,4- or 2,3-butylene oxide, and the like.
[0054] When the resin (A) is a resin having a carboxyl group and / or a 1,3-dioxo-2-oxapropylene group {for example, a resin obtained by a reaction using an aromatic compound having a carboxyl group or an aromatic compound having a 1,3-dioxo-2-oxapropylene group, specifically, polyarylate resin (A2), aromatic polyimide resin (A5), aromatic polyetherimide resin (A6), etc.}, examples of the resin include a reaction product of a carboxyl group and an alkylene oxide. A modified product having a (poly)oxyalkylene group can be obtained by a reaction with an alkylene oxide, and a sulfo group (-SO3H) can be added to a hydroxyl group by a reaction with at least one of sulfamic acid, chlorosulfuric acid, and sultones.
[0055] When the resin (A) is a resin having an amino group {for example, a resin obtained by a reaction using an aromatic compound having an amino group is included, specifically, aromatic polyimide resin (A5), aromatic polyetherimide resin (A6), etc.}, examples of the reaction product include a reaction product of an amino group with at least one selected from the group consisting of an alkylene oxide, sulfamic acid, chlorosulfuric acid, and sultones (for example, 1,3-propane sultone, etc.). A modified product having a (poly)oxyalkylene group can be obtained by the reaction with an alkylene oxide, and a sulfo group (-SO3H) can be added to a hydroxyl group by the reaction with at least one of sulfamic acid, chlorosulfuric acid, and sultones.
[0056] A modified resin in which a carboxyl group and / or a 1,3-dioxo-2-oxapropylene group has been introduced into resin (A) can be obtained by heating and mixing resin (A) with an unsaturated carboxylic acid and / or its acid anhydride, and allowing the addition reaction to occur. The unsaturated carboxylic acid includes an unsaturated monocarboxylic acid and an unsaturated dicarboxylic acid. Examples of the unsaturated monocarboxylic acid include linear aliphatic unsaturated monocarboxylic acids having 3 to 24 carbon atoms (acrylic acid, methacrylic acid, etc.), alicyclic unsaturated monocarboxylic acids having 7 to 24 carbon atoms (cyclohexene carboxylic acid, cycloheptene carboxylic acid, bicycloheptene carboxylic acid, methyltetrahexene carboxylic acid, etc.), and aromatic unsaturated monocarboxylic acids having 7 to 24 carbon atoms (4-vinylbenzoic acid, etc.). Examples of the unsaturated dicarboxylic acid include chain aliphatic dicarboxylic acids having 4 to 24 carbon atoms (maleic acid, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, etc.), and alicyclic dicarboxylic acids having 8 to 24 carbon atoms (cyclohexene dicarboxylic acid, cycloheptene dicarboxylic acid, bicycloheptene dicarboxylic acid, methyltetrahydrophthalic acid, etc.). Of these, maleic acid, maleic anhydride and fumaric acid are preferred.
[0057] When the resin (A) is a polyphenylene ether resin (A1), for example, the methods described in JP-A-8-311196 and JP-A-2005-8829 can be used. Specifically, for example, the polyphenylene ether resin (A1) and an unsaturated carboxylic acid and / or its acid anhydride can be reacted by melt kneading at a temperature of 150 to 350°C using a twin-screw extruder, a roll mill, etc. in the presence of a radical generator (benzoyl peroxide, di-t-butyl peroxide, dicumyl peroxide, t-butyl peroxybenzoate, azobisisobutyronitrile, azobisisovaleronitrile, 2,3-diphenyl-2,3-dimethylbutane, etc.), or by heating and reacting in a solvent (for example, benzene, toluene, xylene, etc.).
[0058] From the viewpoint of strength of the molded article, the modified material (B) is preferably a modified resin obtained by introducing at least one group selected from the group consisting of a sulfo group, a carboxyl group, and a 1,3-dioxo-2-oxapropylene group into the resin (A).
[0059] In the modified product (B), the oxyalkylene group is preferably an oxyethylene group or a combination of an oxyethylene group and an oxypropylene group, more preferably an oxyethylene group, from the viewpoint of emulsion stability.
[0060] From the viewpoint of emulsion stability, the modified product (B) preferably has 5 to 50% by weight, and more preferably 7 to 40% by weight, of oxyalkylene groups based on the weight of the modified product (B).
[0061] The glass transition temperature (hereinafter sometimes abbreviated as Tg) of the modified product (B) is preferably from 10 to 350°C, more preferably from 100 to 300°C, from the viewpoints of moldability and strength of the molded product.
[0062] The Mw of the modified product (B) is preferably from 1,500 to 30,000, and more preferably from 1,700 to 25,000, from the viewpoint of bundling ability.
[0063] In the present invention, the average number of hydroxyl groups per molecule in the resin (A) is preferably 1.5 or more from the viewpoint of emulsion stability. From the viewpoint of emulsion stability, the total average number of hydroxyl groups, sulfo groups and carboxyl groups per molecule in all modified substances (B) contained in the fiber sizing agent of the present invention is preferably 1.5 or more, more preferably 2 to 10. In the present invention, one 1,3-dioxo-2-oxapropylene group (acid anhydride group) is calculated as two carboxyl groups. The average number of hydroxyl groups, sulfo groups and carboxyl groups per molecule can be measured by Mn, hydroxyl value, strong acid value and acid value. Specifically, the average number of hydroxyl groups per molecule can be calculated from the hydroxyl value (JIS K0070, pyridine-acetyl chloride method) and Mn (the above-mentioned GPC measurement conditions) of the modified product (B) by the following formula: Average number of hydroxyl groups per molecule = Mn / 56100 x hydroxyl value The average number of sulfo groups per molecule can be calculated from the strong acid value and Mn (the above-mentioned GPC measurement conditions) of the modified product (B) by the following formula. Average number of sulfo groups per molecule = Mn / 56100 x strong acid value When the resin (A) is a resin whose hydroxyl value is difficult to measure, such as the polyphenylene ether resin (A1) and the polyarylate resin (A2), the hydroxyl value can be measured by the method described below.
[0064] <Method for measuring strong acid value> In accordance with JIS K0070-1992 (neutralization titration method), thymol blue indicator is used as the indicator, and titration is performed with KOH titration solution. The end point is the point at which the color changes from red to yellow and continues for approximately 30 seconds, and the strong acid value is calculated using the number of mL of KOH titration solution (S) required for the titration using the following formula. Note that if the sample remains yellow even after the indicator is added, the strong acid value is considered to be 0. Strong acid value = S x f x Y S: The number of ml of KOH titration solution required for the titration f: Potency of KOH titration solution Y: If the KOH solution used for titration is 0.1 mol / L, use 5.61. If it is 0.01 mol / L, use 0.561.
[0065] The average number of carboxyl groups per molecule can be calculated from the acid value, strong acid value and Mn (the above-mentioned GPC measurement conditions) of the modified product (B) by the following formula. Average number of carboxyl groups per molecule = Mn / 56100 x (acid value - strong acid value) The acid value in the present invention is a value obtained by measuring according to the following procedures (1) to (3) in accordance with JIS K0070. <Acid value measurement method> (1) Dissolve 1 g of (X) in 100 g of THF adjusted to 100°C. (2) At the same temperature, titration is performed with 0.1 mol / L potassium hydroxide aqueous solution [product name "0.1 mol / L potassium hydroxide aqueous solution", manufactured by Wako Pure Chemical Industries, Ltd.] using phenolphthalein as an indicator. (3) Convert the amount of potassium hydroxide required for the titration into mg to calculate the acid value (unit: mgKOH / g). The acid value of the modified product (B) is preferably from 5 to 112 mgKOH / g, more preferably from 10 to 80 mgKOH / g, from the viewpoint of emulsion stability.
[0066] In the present invention, when the modified material (B) is heated in nitrogen up to 500°C under conditions of a heating start temperature of 30°C and a heating rate of 5°C / min, the heating weight loss ratio at 400°C (hereinafter abbreviated as heating weight loss ratio (400°C)) is 20% by weight or less, preferably 10% by weight or less, and more preferably 8% by weight or less, from the viewpoint of the appearance and strength of the molded product. If the heating weight loss ratio exceeds 20% by weight, gas, which is a component derived from heating weight loss, is generated during molding, which may deteriorate the appearance on the surface of the molded product and cause a decrease in strength due to void formation inside the molded product. The heating weight loss ratio (400°C) can be determined by using a heating weight loss analyzer ("TG / DTA6200" [Seiko Instruments Inc.]) to heat approximately 10 mg of a sample in nitrogen from 30°C to 500°C at a rate of 5°C / min, and analyzing the resulting TG curve to calculate the heating weight loss ratio at 400°C based on the weight of the sample used in the measurement (measurement atmosphere: nitrogen at 200 ml / min, sample container: aluminum pan). The heat loss ratio (400°C) can be reduced by improving the aromatic ring concentration or molecular weight of the modified product (B), specifically by reducing the amount of oxyalkylene groups in (B), by using a modified product (B) of a resin (A) with a high molecular weight, or by using a modified product (B) of a resin (A) with fewer substituents such as alkyl groups. In the fiber sizing agent of the present invention, the heat loss ratio (400°C) of the resin (A) and the modified substance (B) is 10% by weight or less, so that defects are not generated in the molded product, and the appearance and strength of the molded product can be improved.
[0067] The fiber sizing agent of the present invention may contain, in addition to the modified substance (B), a surfactant (C) and other additives.
[0068] Examples of the surfactant (C) include nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, etc. The surfactant (C) may be used alone or in combination of two or more kinds. Of the surfactants (C), from the viewpoint of ease of preparation of an aqueous emulsion, anionic surfactants, nonionic surfactants, and combinations of these are preferred. More preferred are alkylene oxide adducts of alkyl (preferably alkyl groups having 9 to 15 carbon atoms) phenols, alkylene oxide adducts of arylalkyl (preferably alkyl groups having 2 to 10 carbon atoms) phenols (styrenated phenol, styrenated cumylphenol, styrenated cresol, etc.), sulfate salts of the alkylene oxide adducts of the alkylphenols, sulfate salts of the alkylene oxide adducts of the arylalkylphenols, urethane joint compounds of the alkylene oxide adducts of the arylalkylphenols and polyethylene glycols, and mixtures thereof. Particularly preferred are alkylene oxide adducts of arylalkylphenols, sulfate salts of alkylene oxide adducts of arylalkylphenols, and mixtures thereof.
[0069] Other additives include neutralizing agents, smoothing agents, preservatives, and antioxidants. Examples of the neutralizing agent include potassium hydroxide, sodium hydroxide, magnesium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, calcium carbonate, calcium bicarbonate, magnesium carbonate, magnesium bicarbonate, monolaurylamine, trimethylamine, dimethylmonoethanolamine, triethanolamine, ethylenediamine, and ammonia. Examples of the smoothing agent include waxes (polyethylene, polypropylene, oxidized polyethylene, oxidized polypropylene, modified polyethylene, modified polypropylene, etc.), higher fatty acid (fatty acid having 6 to 30 carbon atoms) alkyl (alkyl having 1 to 24 carbon atoms) esters (methyl stearate, ethyl stearate, propyl stearate, butyl stearate, octyl stearate, stearyl stearate, etc.), higher fatty acids (fatty acid having 6 to 30 carbon atoms) (myristic acid, palmitic acid, stearic acid, etc.), natural fats and oils (coconut oil, beef tallow, olive oil, rapeseed oil, etc.), and liquid paraffin. Preservatives include benzoic acid, salicylic acid, sorbic acid, quaternary ammonium salts, and imidazole. Antioxidants include phenols (such as 2,6-di-t-butyl-p-cresol), thiodipropionates (such as dilauryl 3,3'-thiodipropionate), and phosphites (such as triphenyl phosphite).
[0070] From the viewpoint of emulsion stability, the weight proportion of the modified substance (B) is preferably 40 to 99.5% by weight, more preferably 50 to 99% by weight, and particularly preferably 60 to 98.5% by weight, based on the weight of the solid content contained in the fiber sizing agent. From the viewpoint of emulsion stability, the weight proportion of the surfactant (C) is preferably 0.1 to 40% by weight, more preferably 0.5 to 35% by weight, and particularly preferably 1 to 30% by weight, based on the weight of the solid content contained in the fiber sizing agent. The total weight proportion of the neutralizing agent, smoothing agent, preservative and antioxidant as other additives is preferably 0.01 to 20% by weight, more preferably 0.05 to 15% by weight, and particularly preferably 0.1 to 10% by weight, based on the weight of the solid content contained in the fiber sizing agent, from the viewpoints of fluidity and stability over time. Here, the solid content refers to the residue remaining after heating and drying 1 g of the sample at 130° C. for 45 minutes in a circulating air dryer.
[0071] The fiber sizing agent of the present invention preferably contains an aqueous medium so as to be in the form of an aqueous solution or an aqueous emulsion. When an aqueous medium is contained, it is easy to adjust the amount of solid matter contained in the fiber sizing agent to adhere to the fibers to an appropriate amount, so that a fiber bundle having even greater strength in a molded body of the composite material can be obtained. As the aqueous medium, known aqueous media can be used, and specific examples thereof include water and hydrophilic organic solvents [monohydric alcohols having 1 to 4 carbon atoms (methanol, ethanol, isopropanol, etc.), ketones having 3 to 6 carbon atoms (acetone, ethyl methyl ketone, methyl isobutyl ketone, etc.), glycols having 2 to 6 carbon atoms (ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, etc.) and their monoalkyl (carbon number 1 to 2) ethers, dimethylformamide, and alkyl acetates having 3 to 5 carbon atoms (methyl acetate, ethyl acetate, etc.)]. These may be used in combination of two or more kinds. Among these, from the viewpoint of safety etc., water and a mixed solvent of a hydrophilic organic solvent and water are preferred, and water is more preferred.
[0072] From the viewpoint of cost, etc., it is preferable that the fiber sizing agent of the present invention is distributed at a high concentration and is distributed at a low concentration when a fiber bundle is produced. That is, by distributing the agent at a high concentration, transportation costs and storage costs can be reduced, and by treating the fibers at a low concentration, a fiber bundle that can increase the strength of a molded body of a composite material can be produced. The concentration of the high-concentration aqueous solution or emulsion (weight ratio of solid content to fiber sizing agent) is preferably 20 to 80% by weight, and more preferably 30 to 70% by weight, from the viewpoint of storage stability and the like. On the other hand, the concentration of the low-concentration aqueous solution or emulsion (weight ratio of solids to the fiber bundling agent) is preferably 0.5 to 15% by weight, and more preferably 1 to 10% by weight, from the viewpoint of ensuring an appropriate amount of sizing agent adhered during the production of fiber bundles.
[0073] The fiber sizing agent of the present invention can be produced by mixing the modified substance (B) with, if necessary, an aqueous medium, a surfactant (C) and other additives in any order. When an aqueous solvent is included, it is preferable to mix the components other than the aqueous medium in advance, and then add the aqueous medium to the mixture obtained to dissolve or emulsify the mixture.
[0074] When components other than the aqueous medium are mixed in advance, the temperature is preferably 20 to 90° C., more preferably 40 to 90° C., from the viewpoint of ease of mixing, and the same is also true for the temperature of the subsequent dissolution or emulsification dispersion. The time for the dissolving or emulsifying / dispersing is preferably 1 to 20 hours, and more preferably 2 to 10 hours.
[0075] There are no limitations on the mixing equipment, dissolving equipment, and emulsifying / dispersing equipment, and examples that can be used include stirring blades (blade shape: paddle type and three-stage paddle, etc.), Nauta mixers, ribbon mixers, conical blenders, mortar mixers, universal mixers (Universal Mixing Agitator 5DM-L, manufactured by San-Ei Seisakusho Co., Ltd., etc.), and Henschel mixers.
[0076] Examples of fibers to which the fiber sizing agent of the present invention can be applied include known fibers such as glass fibers, carbon fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, rock fibers, and slug fibers (such as those described in International Publication No. 2003 / 47830), and from the viewpoint of improving the strength of a molded body of a composite material, the fiber is preferably at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers, and more preferably carbon fibers. Two or more types of these fibers may be used in combination.
[0077] The fiber bundle of the present invention is a fiber bundle (a fiber bundle of approximately 3,000 to 50,000 fibers) obtained by treating at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, and slug fibers with the fiber sizing agent of the present invention. That is, the fiber bundle of the present invention contains at least one type of fiber selected from the group consisting of carbon fibers, glass fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers and slug fibers, and the modified material (B).
[0078] The fiber treatment method may be a spray method or a dipping method. The amount (wt%) of the solid content of the fiber sizing agent adhered to the fiber is preferably 0.05 to 5 wt%, more preferably 0.2 to 2.5 wt%, based on the weight of the fiber. Within this range, the strength of the molded body (hereinafter sometimes referred to as a composite material) can be further improved.
[0079] The textile product of the present invention is a product made using the fiber bundle, and includes textile products obtained by processing the fiber bundle, such as woven fabrics, knitted fabrics, nonwoven fabrics (felt, mats, papers, etc.), chopped fibers, and milled fibers.
[0080] The resin composition of the present invention is a resin composition containing the fiber bundle and / or fiber product and a thermoplastic resin (E). From the viewpoint of the strength of the composite material to be molded, the weight ratio of the thermoplastic resin (E) to the fiber bundles and fiber products (matrix resin / fiber bundles and fiber products) is preferably 10 / 90 to 90 / 10, more preferably 20 / 80 to 70 / 30, and particularly preferably 30 / 70 to 60 / 40.
[0081] The thermoplastic resin (E) may be at least one selected from the group consisting of phenol resins, melamine resins, urea resins, polyimide resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyetherketoneketone resins, and polyphenylene sulfide resins. Among these, from the viewpoint of strength of the molded product, polyimide resins, polyamideimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyetherketoneketone resins, and polyphenylene sulfide resins are preferred, and polyimide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, and polyetheretherketone resins are more preferred.
[0082] The molded article of the present invention is obtained by molding the above-mentioned resin composition of the present invention. The molding method for the molded article of the present invention is not particularly limited by the heat molding method, and examples thereof include a filament winding molding method (a method in which a material is wound around a rotating mandrel under tension and then heat molded), a press molding method (a method in which prepreg sheets are laminated and then heat molded), an autoclave method (a method in which a prepreg sheet is pressed against a mold under pressure and then heat molded), and a method in which chopped fibers or milled fibers are mixed with a thermoplastic resin to form a resin composition, which is then injection molded. EXAMPLES
[0083] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, % means % by weight and parts means parts by weight. Examples 1 to 4 below are reference examples.
[0084] <Production Example 1: Production of polyphenylene ether resin (A-1)> In a 1.5-liter jacketed reactor equipped with a sparger for introducing an oxygen-containing gas at the bottom of the reactor, stirring turbine blades and baffles, and a reflux condenser on the vent gas line at the top of the reactor, 0.271 g of cupric chloride dihydrate, 1.20 g of 35% hydrochloric acid, 10.6 g of N,N,N',N'-tetramethylpropanediamine, 230 g of n-butanol and 535 g of methanol, 164 g of 2,6-dimethylphenol (referred to as "2,6-xylenol" in Table 1), and 32.0 g of 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane (referred to as "bisphenol" in Table 1) were placed. The composition weight ratio of the solvents used was n-butanol:methanol = 30:70. Next, oxygen was introduced into the reactor from the sparger at a rate of 180 mL / min while vigorously stirring, and at the same time, a heat medium was passed through the jacket to maintain the polymerization temperature at 45°C. The polymerization solution gradually took on the form of a slurry. 120 minutes after the start of oxygen introduction, the aeration of the oxygen-containing gas was stopped, and a 50% aqueous solution of 1.40 g of ethylenediaminetetraacetic acid tripotassium salt (a reagent manufactured by Dojindo Laboratories) was added to the polymerization mixture, followed by the addition of 1.75 g of hydroquinone (a reagent manufactured by Wako Pure Chemical Industries, Ltd.) in small portions, and the reaction was carried out at 45°C for 1 hour until the slurry-like polyphenylene ether turned white. After the reaction was completed, the mixture was filtered and washed three times with a methanol washing solution (b) in an amount such that the mass ratio (b / a) of the washed polyphenylene ether (a) to the methanol washing solution (b) was 4, and then the mixture was vacuum-dried at 120°C for 1 hour to obtain polyphenylene ether resin (A-1). The analysis results of (A-1) are shown in Table 1.
[0085] <Production Example 2: Production of polyphenylene ether resin (A-2)> A polyphenylene ether resin (A-2) was obtained in the same manner as in Example 1, except that the phenolic compounds used were 136 g of 2,6-dimethylphenol and 64.0 g of 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane. The analytical results are shown in Table 1.
[0086] <Production Example 3: Production of polyphenylene ether resin (A-3)> A polyphenylene ether resin (A-3) was obtained in the same manner as in Example 2, except that the amines used were 5.20 g of dibutylamine and 8.80 g of N,N,N',N'-tetramethylpropanediamine. The analytical results are shown in Table 1.
[0087] [Table 1]
[0088] <Production Example 4: Production of polyarylate resin (A-4)> In a reaction vessel equipped with a stirrer, 20 g of 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as Bis A), 9.74 g of sodium hydroxide (hereinafter referred to as NaOH), and 3.36 g of tri-n-butylbenzylammonium chloride (hereinafter referred to as TBBAC) were charged and dissolved in 59.2 ml of pure water to prepare an aqueous phase. Separately, 16.48 g of a 50 / 50 mixture of terephthalic acid dichloride / isophthalic acid dichloride was dissolved in 350 ml of dichloromethane as an aromatic dicarboxylic acid to prepare an organic phase. First, while stirring the aqueous phase at a rotation speed of 400 rpm, the organic phase was gradually dripped at 20 ml / sec, and then stirring was continued for 4 hours to perform interfacial polycondensation. The temperature was kept at 15°C during stirring to polymerize. After 4 hours, stirring was stopped, and the aqueous phase was separated and removed after being left to stand. Next, 550 ml of pure water and 2.74 ml of acetic acid were added to the organic phase, and the mixture was stirred again at 400 rpm for 30 minutes. After 30 minutes, the stirring was stopped, and the mixture was left to stand, after which the aqueous phase was removed. After the washing operation of adding pure water and stirring was repeated until the remaining organic phase became neutral, 137.4 ml of dichloromethane was added to the organic phase, and the insoluble matter was removed through a 2 μmφ filter to obtain a resin solution. This resin solution was gradually added to 2060 ml of methanol while stirring to precipitate the resin, and after the entire amount was dropped, stirring was continued for another 30 seconds. The stirring was stopped, the precipitated resin was separated, and the mixture was dried under reduced pressure at 80°C and 13 Pa for 12 hours to obtain polyarylate resin (A-4). The analysis results are shown in Table 2.
[0089] <Production Example 5: Production of polyarylate resin (A-5)> A polyarylate resin (A-5) was obtained in the same manner as in Production Example 4, except that 12.7 g of 1,1-bis(4-hydroxyphenyl)-1-phenylethane (hereinafter referred to as BisAP) and 11.0 g of bis(4-hydroxyphenyl)sulfone (hereinafter referred to as BisS) were added as dihydric phenol components. The analysis results are shown in Table 2.
[0090] <Production Example 6: Production of polysulfone resin (A-6)> In a reaction vessel equipped with a stirrer, a nitrogen inlet tube, a thermometer, and a condenser, 77.02 parts by mass of 4,4'-dichlorodiphenylsulfone, 75.08 parts by mass of 4,4'-dihydroxydiphenylsulfone (bisphenol S), 43.54 parts by mass of potassium carbonate, and 165 parts by mass of N-methyl-2-pyrrolidone (hereinafter abbreviated as "NMP") were mixed and reacted at 190 ° C for 6 hours. Next, the obtained reaction mixture solution was diluted with NMP and cooled to room temperature to precipitate unreacted potassium carbonate and by-produced potassium chloride. By reducing these inorganic salts by filtration, a polysulfone solution in which polysulfone was dissolved in NMP was obtained. Furthermore, this solution was dropped into water to precipitate polysulfone, and unnecessary NMP was reduced by filtration to obtain a precipitate. The obtained precipitate was repeatedly washed with methanol and dried by heating at 150 ° C to obtain a polysulfone resin (A-6). Analysis of the polysulfone resin (A-6) revealed that it had an Mw of 7,000, an average number of hydroxyl groups per molecule of 2, and a glass transition temperature of 170°C.
[0091] <Production Example 7: Production of polyethersulfone resin (A-7)> ' 214.22 parts by weight of powdered 4,4'-dihydroxybenzophenone, 500 ml of 4N potassium hydroxide aqueous solution, and 200 parts by weight of methanol were charged into a reaction vessel equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, and stirred at room temperature for 1 hour. At this time, the contents of the reaction vessel were a pale yellow homogeneous solution. This solution was transferred to an eggplant-shaped flask, and methanol and most of the water were removed using a rotary evaporator. The obtained solid was pulverized to a fine powder of 0.150 mmφ or less, and the water was removed using a vacuum dryer. After drying, the content of the dipotassium salt of 4,4'-dihydroxybenzophenone was analyzed by neutralization titration method, and it was 94.8% by weight. Next, 61.3 parts by weight of powdered dipotassium salt of 4,4'-dihydroxybenzophenone with a content of 94.8% by weight and 106.7 parts by weight of diphenyl sulfone were charged into a reaction vessel equipped with a stirrer, nitrogen inlet tube, thermometer, and condenser, and heated to 230°C. Next, water was completely removed under reduced pressure, and nitrogen was introduced to return to normal pressure. Next, 52.22 parts by weight of powdered 4,4'-dichlorodiphenylsulfone and 40.00 parts by weight of diphenylsulfone were charged, and the temperature was raised to 290°C while flowing nitrogen. The mixture was stirred at the same temperature for 8 hours while flowing nitrogen. After that, the mixture was cooled to room temperature, and the solidified reaction mixture was pulverized, washed repeatedly with methanol, and dried at 150°C to obtain polyethersulfone resin (A-7). Analysis of polyethersulfone resin (A-7) revealed that it had an Mw of 8,000, an average number of hydroxyl groups per molecule of 2, and a glass transition temperature of 205°C.
[0092] <Production Example 8: Production of aromatic polyimide resin (A-8)> In a pressure-resistant reaction vessel equipped with a stirrer, a nitrogen inlet tube, a thermometer, and a condenser, 44.21 g (0.12 mol) of 4,4'-bis(3-aminophenoxy)biphenyl, 24.58 g (0.1127 mol) of pyromellitic dianhydride, 2.17 g (0.01416 mol) of phthalic anhydride, and 212.9 g of distilled water were charged, and the inside of the pressure-resistant reaction vessel was sufficiently replaced with nitrogen while stirring. The temperature was raised to 180°C. The internal pressure at this time was about 0.8 MPa. After this, the mixture was stirred at 180°C (0.8 MPa) for 3 hours. After cooling, water was distilled off from the reaction system, and the mixture was dried in nitrogen at 300°C for 8 hours to obtain an aromatic polyimide resin (A-8). Analysis of the aromatic polyimide resin (A-8) revealed that it had a Mw of 16,000, an average number of hydroxyl groups per molecule of 0, and a glass transition temperature of 210°C.
[0093] <Production Example 9: Production of aromatic polyetherimide resin (A-9)> In a pressure-resistant reaction vessel equipped with a stirrer, a nitrogen inlet tube, a thermometer and a condenser, 43 parts by weight of 2,2'-bis(4-(4-aminophenoxy)phenyl)propane, 52 parts by weight of 2,2-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride, 1000 parts by weight of N-methylpyrrolidone and 300 parts by weight of toluene were charged, and the mixture was stirred at room temperature for 1 hour, then heated to 150°C and refluxed and stirred for another 1 hour. The mixture was further heated to 180°C while distilling off the toluene, and then cooled. The reaction liquid was poured into methanol, the polymer was isolated, washed repeatedly with methanol and dried at 150°C to obtain an aromatic polyetherimide resin (A-9). Analysis of the aromatic polyetherimide resin (A-9) revealed that it had an Mw of 11,000, an average number of hydroxyl groups per molecule of 0, and a glass transition temperature of 195°C.
[0094] <Production Example 10: Production of aromatic polyether ketone resin (A-10)> In a reaction vessel equipped with a stirrer and a nitrogen inlet tube, 10.66 parts by weight of 4,4'-dichlorobenzophenone, 6.46 parts by weight of 1,3-bis(4-chlorobenzoyl)benzene, 16.76 parts by weight of 4,4'-biphenol, 13.06 parts by weight of potassium carbonate, and 100 parts by weight of diphenyl sulfone were placed, and nitrogen was blown in to raise the temperature to 140°C to dissolve the diphenyl sulfone. The temperature was raised to 250°C in 50 minutes, and polymerization was carried out at this temperature for 90 minutes and 340°C in 40 minutes, and the temperature was maintained for 35 minutes, and the reaction solution was poured into a stainless steel tray and solidified. The solidified reaction mixture was crushed, repeatedly washed with methanol, and dried at 150°C to obtain aromatic polyether ketone resin (A-10). Analysis of aromatic polyether ketone resin (A-10) showed that Mw was 1,100, the average number of hydroxyl groups per molecule was 2, and the glass transition temperature was 130°C.
[0095] <Production Example 11: Production of aromatic polyether ether ketone resin (A-11)> A pressure-resistant reaction vessel equipped with a stirrer and a nitrogen inlet tube was charged with 32.73 parts by weight of 4,4'-difluorobenzophenone, 17.18 parts by weight of hydroquinone, 90.15 parts by weight of diphenyl sulfone, and 15.05 parts by weight of potassium carbonate. Nitrogen was then blown in and the temperature was raised to 140°C to dissolve the diphenyl sulfone. The temperature was raised to 250°C in 50 minutes, and polymerization was carried out at this temperature for 90 minutes and 340°C in 40 minutes, and the temperature was maintained for 35 minutes. The reaction solution was poured into a stainless steel tray and solidified. The solidified reaction mixture was crushed, repeatedly washed with methanol, and dried at 150°C to obtain an aromatic polyether ether ketone resin (A-11). Analysis of the aromatic polyether ether ketone resin (A-11) revealed that it had an Mw of 9,000, an average number of hydroxyl groups per molecule of 2, and a glass transition temperature of 135°C.
[0096] <Comparative Production Example 1: Production of polyarylate resin (A'-1)> In a reaction vessel equipped with a stirring device, 42.7 g of bisphenol A as a divalent phenol component, 0.800 g of p-tert-butylphenol (PTBP) as a terminal blocking agent, 16.3 g of NaOH as an alkali, 0.730 g of a 50% by mass aqueous solution of TBBAC as a polymerization catalyst, and 0.260 g of sodium hydrosulfite as an antioxidant were charged and dissolved in 1250 parts by mass of water (aqueous phase). Separately, 37.9 g of a mixture of isophthaloyl chloride / terephthaloyl chloride = 1 / 1 (molar ratio) (MPC) was dissolved in 1000 g of methylene chloride (organic phase). The aqueous phase was stirred in advance, the organic phase was added to the aqueous phase under strong stirring, and polymerization was carried out by an interfacial polymerization method at 15 °C for 2 hours. Thereafter, stirring was stopped, and the aqueous phase and the organic phase were separated by decantation. After removing the aqueous phase, 250 g of methylene chloride, 1500 g of pure water, and 5.00 g of acetic acid were added to stop the reaction, and the mixture was stirred at 15 °C for 30 minutes. Thereafter, the organic phase was washed 10 times with pure water, and the organic phase was added to methanol to precipitate the polymer. After filtering the precipitated polymer, vacuum drying was carried out at 165 °C for 24 hours to obtain a polyarylate resin (A'-1). The analysis results are shown in Table 2.
[0097]
Table 2
[0098] <Measurement Method of Mw of Resins (A―1) to (A-11), Resin (A'-1), Modified Products (B-1) to (B-19), and Modified Products (B'-1) to (B'-3)> The Mw of each resin and the Mw of each modified product were determined by polystyrene conversion under the following conditions using gel permeation chromatography (GPC). <Measurement Conditions of GPC> Liquid Delivery Device: Waters, Isocratic HPLC Pump 1515 Detector: Waters, Refractive Index Detector 2414 Column: Mixed-D (packed silica gel particle size 5 μm, tube length 300 mm, inner diameter 7.5 mm) Solvent: Chloroform Flow rate: 1mL / min Measurement temperature: 35℃
[0099] <Method for measuring the average number of hydroxyl groups per molecule of polyphenylene ether resin> 5.0 mg of polyphenylene ether resin was weighed out. The weighed polyphenylene ether resin was dissolved in 25 mL of methylene chloride. 150 μL of 2 mass% tetraethylammonium hydroxide (TEAH) ethanol solution was added to 2.0 mL of the prepared solution, and then the absorbance (Abs) at 318 nm was measured using a UV spectrophotometer (Hitachi: U-3210 type) (a cell for measuring absorbance with a cell length of 1 cm was used). Based on the measurement results, the pseudo molecular weight obtained from the absorbance was calculated by the following formula: The average number of hydroxyl groups per molecule of the polyphenylene ether resin was calculated using the number average molecular weight obtained by gel permeation chromatography in the above-described method. The pseudo molecular weight obtained from absorbance (g / mol) = [((ε × 5) / (25 × Abs)], where ε is the extinction coefficient, which is 4700 L / mol cm. Number of hydroxyl groups per molecule of polyphenylene ether (number / molecule) = (number average molecular weight determined by gel permeation chromatography) / (pseudo molecular weight obtained from absorbance)
[0100] <Method for measuring the average number of hydroxyl groups per molecule of polyarylate resin> Using a high-resolution nuclear magnetic resonance spectrometer (JEOL LA-400 NMR), 1 The composition and molar ratio of the monomer components constituting the polyarylate resin were determined from the peak areas of each by H-NMR analysis. The amount of hydroxyl groups (mol%) was quantified from the peak area of the protons located at the ortho or meta positions relative to the phenolic hydroxyl groups. The average number of hydroxyl groups was calculated from the obtained amount of hydroxyl groups (mol%) and the Mn of the polyarylate resin by the following formula. NMR measurement conditions Resolution: 400MHz Solvent: A mixture of deuterated trifluoroacetic acid and deuterated tetrachloroethane in a volume ratio of 1 / 11 Temperature: 50℃ Average number of hydroxyl groups per molecule of polyarylate resin = Hydroxyl group amount (mol%) × Mn / 100
[0101] <Method for measuring the average number of hydroxyl groups per molecule of resins (A-6) to (A-11)> The average number of hydroxyl groups per molecule of each resin was determined by the same method as in the above "Method for measuring the average number of hydroxyl groups per molecule of polyarylate resin".
[0102] <Method of measuring glass transition temperature (Tg) of resins (A-1) to (A-11), resin (A'-1), modified products (B-1) to (B-19) and modified products (B'-1) to (B'-3)> The Tg of each resin and each modified product was measured in accordance with JIS K7121 (1987) using a differential scanning calorimeter (DSC) (e.g., Shimadzu DSC-60 manufactured by Shimadzu Corporation) by heating from 40 to 300°C at a rate of 20°C / min under a nitrogen atmosphere.
[0103] <Production Example 12> In a glass autoclave, 100 g of the polyphenylene ether resin (A-1) obtained in Production Example 1 and 100 g of methyl ethyl ketone (hereinafter referred to as MEK) were charged and uniformly dissolved at 150 ° C., and then 20 g of EO charged in a pressure-resistant dropping funnel was dropped over 6 hours while controlling the reaction temperature to be kept at 135 to 150 ° C., and then the mixture was aged for another 3 hours at 135 ° C. Then, MEK was distilled off to obtain a modified product (B-1). Since the weight of the obtained (B-1) was 120 g, all of the charged EO had reacted, and the content of oxyalkylene groups was calculated from the amount of EO charged and the weight of the obtained (B-1). The analysis results are shown in Table 3.
[0104] <Production Examples 13 to 18, Production Examples 25 to 26, Production Examples 29 to 30, Comparative Production Examples 2 to 4> In Production Example 12, modified products (B-2) to (B-7), (B-14), (B-15), (B-18), (B-19) and modified products (B'-1) to (B'-3) were obtained by performing the same operations as in Production Example 12, except that the type and amount of resin (A) used and the type and amount of alkylene oxide used were changed to those shown in Table 3 or Table 4. The analytical results are shown in Table 3 or Table 4.
[0105] <Production Example 19> 2042 g of orthodichlorobenzene was placed in a flask equipped with a stirrer, and 100 g of the polyphenylene ether resin (A-1) obtained in Production Example 1 was added thereto and stirred at 90°C. After (A-1) was completely dissolved in orthodichlorobenzene, it was cooled, and a mixed solution of 29.9 g of chlorosulfonic acid and 46.0 g of sulfolane was dropped at 40°C over 30 minutes, and the mixture was kept at 40°C for 4.5 hours. No precipitate was observed in the solution. Then, the reaction solution was dropped into 3.2 L of ion-exchanged water, and the slurry containing white particles was filtered. This slurry was washed and filtered with heptane and ion-exchanged water, and this was repeated until the pH of the filtrate reached 5.0 or more, and then dried in a reduced pressure dryer at a temperature of 80°C and a pressure of 7 kPa or less for 24 hours to obtain a modified product (B-8). The analysis results are shown in Table 3.
[0106] <Production Examples 20-21> Modified products (B-9) and (B-10) were obtained by the same procedure as in Production Example 19, except that the type and amount of resin (A) and the amount of chlorosulfonic acid used in Production Example 19 were changed to those shown in Table 3. The analytical results are shown in Table 3.
[0107] <Production Example 22> 100g of the polyphenylene ether resin (A-1) obtained in Production Example 1 and 3.7g of maleic anhydride were charged into a reaction vessel, and after replacing with nitrogen, the vessel was heated to 180°C under nitrogen aeration to dissolve uniformly. A solution of 0.5g of a radical generator [dicumyl peroxide, trade name "Percumyl D", manufactured by NOF Corp.] (C-1) dissolved in 5g of xylene was added dropwise thereto over 5 minutes, and the mixture was stirred at 150°C for 3 hours. Thereafter, unreacted maleic anhydride was distilled off under reduced pressure (1.5kPa, the same applies below) to obtain a modified product (B-11). The analytical results are shown in Table 3.
[0108] <Production Examples 23-24, 27-28> Modified products (B-12), (B-13), (B-16) and (B-17) were obtained by the same procedure as in Production Example 22, except that the type and amount of resin (A), the amount of radical generator and the amount of maleic anhydride were changed to those shown in Table 3 or Table 4. The analytical results are shown in Table 3 or Table 4.
[0109] [Table 3]
[0110] [Table 4]
[0111] <Method for measuring the average number of hydroxyl groups per molecule of modified substances (B-1) to (B-19) and modified substances (B'-1) to (B'-3)> The hydroxyl value was measured in accordance with JIS K0070 (pyridine-acetyl chloride method), and Mn was measured under the above-mentioned GPC measurement conditions, and calculated from the obtained hydroxyl value and Mn according to the following mathematical formula. Average number of hydroxyl groups per molecule = Mn / 56100 x hydroxyl value
[0112] <Average number of sulfo groups per molecule of modified products (B-1) to (B-19) and modified products (B'-1) to (B'-3)> The average number of sulfo groups per molecule was calculated from the strong acid value and Mn (the above-mentioned GPC measurement conditions) of each modified product according to the following formula. Average number of sulfo groups per molecule = Mn / 56100 x strong acid value
[0113] <Average number of carboxyl groups per molecule of modified products (B-1) to (B-19) and modified products (B'-1) to (B'-3)> The average number of carboxyl groups per molecule was calculated from the acid value, strong acid value, and Mn (the above-mentioned GPC measurement conditions) of each modified product according to the following formula. Average number of carboxyl groups per molecule = Mn / 56100 x (acid value - strong acid value)
[0114] <Method of measuring heat loss ratio> Using a heat loss analysis ("TG / DTA6200" [Seiko Instruments Inc.]), approximately 10 mg of the sample was heated in nitrogen from 30°C to 500°C at a rate of 5°C / min, and the resulting TG curve was analyzed to calculate the heat loss ratio at 400°C based on the weight of the sample used in the measurement (measurement atmosphere: nitrogen at 200 ml / min, sample container: aluminum pan).
[0115] <Example 1> In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 300 parts of (B-1) and 300 parts of MEK were charged, and the mixture was uniformly dissolved at 150° C. under stirring. Further, 700 parts of water was gradually added at 110 to 150° C. over a period of 5 hours to carry out phase inversion emulsification. After cooling to room temperature, MEK was removed under reduced pressure, and water was added so that the solid content was 30.0% by weight, to obtain a fiber sizing agent (X-1).
[0116] <Example 2> In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 290 parts of the modified product (B-1) and 300 parts of MEK were charged, and the temperature was adjusted to 150°C under stirring to dissolve uniformly. Furthermore, 10 parts of a propylene oxide ethylene oxide adduct of styrenated phenol "Soprophor 796 / P" [manufactured by Solvay Nicca Co., Ltd.] (C-1) were charged and mixed uniformly, and then 700 parts of water were gradually added at 110 to 150°C over a period of 5 hours to carry out phase inversion emulsification. After cooling to room temperature, MEK was removed under reduced pressure, and water was added so that the solid content was 30.0% by weight, to obtain a fiber sizing agent (X-2).
[0117] <Examples 3 to 7, Comparative Examples 2 to 3> Fiber sizing agents (X-3) to (X-7), (X'-2) and (X'-3) were obtained by carrying out the same procedure as in Example 1, except that the formulation in Example 1 was changed as shown in Table 5 or Table 6.
[0118] <Examples 8, 15-16, 19-20 and Comparative Example 1> In Example 2, the same procedure as in Example 2 was carried out except that the type and amount of the modified substance and the amount of (C-1) used were those shown in Table 5 or Table 6, to obtain fiber sizing agents (X-8), (X-15) to (X-16), (X-19) to (X-20) and (X'-1).
[0119] <Example 9> In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 300 parts of (B-8), 7.3 parts of sodium hydroxide, and 300 parts of MEK were charged, and the mixture was uniformly dissolved at 150° C. under stirring. Further, 700 parts of water was gradually added at 110 to 150° C. over a period of 5 hours to carry out phase inversion emulsification. After cooling to room temperature, MEK was removed under reduced pressure, and water was added so that the solid content was 30.0% by weight, to obtain a fiber sizing agent (X-9).
[0120] <Examples 10 to 14, 17 to 18> In Example 9, fiber sizing agents (X-10) to (X-14), (X-17) and (X-18) were obtained in the same manner, except that the type and amount of the modified substance and the amount of sodium hydroxide used were those shown in Table 5 or Table 6.
[0121] [Table 5]
[0122] [Table 6]
[0123] <Creating test pieces for evaluating carbon fiber bundles and evaluating bundleability> (1) Fiber sizing agent (X) was further diluted with water to a solid content of 1.5% by weight, and untreated carbon fibers (fineness 800 tex, filament count 12,000) were immersed in the aqueous solution to impregnate the fibers with the sizing agent, and the fibers were dried with hot air at 180°C for 3 minutes to produce carbon fiber bundles. (2) The sizing property of the obtained carbon fiber bundle was evaluated in accordance with JIS L1096-2010 8.21.1 A method (45° cantilever method). The larger the value (cm), the better the focusing ability. The bundle of carbon fibers obtained under these treatment conditions has a bundle focusing ability evaluated with a cantilever of generally 18 cm or more.
[0124] <Creating a molded body> (1) Fiber sizing agent (X) was diluted with water to a solid content concentration of 1.5% by weight, and untreated carbon fibers (fineness 800 tex, filament count 12,000) were immersed in the aqueous solution to impregnate the fibers with the sizing agent, and the carbon fiber bundle obtained by drying with hot air at 180°C for 3 minutes was cut to a length of 6 mm to produce short fiber bundles. The amount of solid content of the fiber sizing agent attached was 1.5% by weight based on the untreated carbon fibers. (2) 70 parts by weight of polyether ether ketone resin (PEEK) [KetaSpire KT-820NT, manufactured by Solvay] was added to 30 parts by weight of the obtained short fiber bundle, and the mixture was dry-blended in a V-type blender. (3) This dry blend was kneaded in a vented twin-screw extruder at 385°C, a rotation speed of 70 rpm, and a residence time of 5 minutes to obtain each resin composition (Y). The resin composition was extruded into a strand shape and cut with a pelletizer to obtain resin pellets of the resin composition. (4) The obtained resin pellets were molded into evaluation test pieces using a Nissei Plastics Industrial Co., Ltd. injection molding machine "PS40EASE" at a cylinder temperature of 385°C and a mold temperature of 150°C.
[0125] <Appearance of molded product> The molded article obtained above was observed under a microscope at 20x magnification, and the appearance was evaluated according to the following criteria. <Evaluation criteria> ◎: No fog at all 〇: Almost no voids (10cm 2 (1 to 5 per ×: Voids are noticeable (10cm 2 (6 or more per
[0126] <Flexural strength of molded product> Using the evaluation test piece obtained above, the bending strength of the molded article was measured in accordance with JIS K 7171. The greater the bending strength of the molded article, the more preferable it is. [Industrial Applicability]
[0127] The fiber sizing agent of the present invention can impart excellent strength to a molded article and has excellent convergence properties, and can therefore be used as a sizing agent for glass fibers, carbon fibers, aramid fibers, ceramic fibers, metal fibers, mineral fibers, or slug fibers. In addition, a fiber bundle or fiber product obtained by treating with the fiber sizing agent composition of the present invention can be used as a reinforcing fiber to obtain a prepreg using a thermoplastic resin as a matrix.
Claims
1. A fiber sizing agent containing a modified product (B) of at least one resin (A) selected from the group consisting of polyarylate resin (A2), polysulfone resin (A3), polyethersulfone resin (A4), aromatic polyimide resin (A5), aromatic polyetherimide resin (A6), aromatic polyetherketone resin (A7), aromatic polyetheretherketone resin (A8) and aromatic polyetherketoneketone resin (A9), wherein the modified product (B) is a modified resin obtained by introducing at least one functional group selected from the group consisting of a (poly)oxyalkylene group, a sulfo group, a carboxyl group and a 1,3-dioxo-2-oxapropylene group into the resin (A), and wherein the modified product (B) has a heat loss ratio of 20% by weight or less at 400°C when heated in nitrogen under conditions of a temperature rise start temperature of 30°C and a temperature rise rate of 5°C / min up to 500°C.
2. The fiber sizing agent according to claim 1, wherein the resin (A) is a polyarylate resin (A2).
3. The fiber sizing agent according to claim 1 or 2, wherein the total average number of hydroxyl groups, sulfo groups and carboxyl groups (one 1,3-dioxo-2-oxapropylene group is calculated as two carboxyl groups) per molecule in all of the modified substances (B) contained in the fiber sizing agent is 1.5 or more.
4. The fiber sizing agent according to any one of claims 1 to 3, wherein the weight average molecular weight of the modified substance (B) is 1,500 to 30,000.
5. A fiber bundle in which at least one type of fiber selected from the group consisting of carbon fiber, glass fiber, aramid fiber, ceramic fiber, metal fiber, mineral fiber, rock fiber, and slag fiber is treated with the fiber sizing agent according to any one of claims 1 to 4.
6. A fiber product comprising the fiber bundle according to claim 5.
7. A resin composition comprising the fiber bundle according to claim 5 and a thermoplastic resin (E).
8. A resin composition comprising the fiber product according to claim 6 and a thermoplastic resin (E).
9. The resin composition according to claim 7 or 8, wherein the thermoplastic resin (E) is at least one selected from the group consisting of a phenol resin, a melamine resin, a urea resin, a polyimide resin, a polyamideimide resin, a polyetherimide resin, a polysulfone resin, a polyethersulfone resin, a polyetheretherketone resin, a polyetherketoneketone resin, and a polyphenylene sulfide resin.
10. A molded article obtained by molding the resin composition according to any one of claims 7 to 9.
Citation Information
Patent Citations
Horiamidomaruchifuiramentomunorizukeshusokushi no seizoho
JP1976035722A
Flame-retardant polystyrene resin composition and polystyrene resin molded article
JP1997031275A
Glass-reinforced styrene-based resin composition
JP1998017740A
Glass fiber for long fiber reinforced thermoplastic resin molding material and long fiber reinforced thermoplastic resin molding material using the glass fiber
JP2003191236A
Binder for glass fiber, glass fiber for olefin resin reinforcement, and method for producing olefin resin composition for fiber-reinforced molding
JP2003253563A